Pragmatic Diversity in Dialogue: Analyzing Maxim Violations and Communication Strategies in The Batman (2022) - Anggraini, Marisa (Cultural Narratives, 2025)
This study investigates the pragmatic phenomenon of maxim violations in the 2022 movie The Batman, employing Grice's cooperative principle as the theoretical framework. Understanding how characters intentionally deviate from conversational norms is crucial for appreciating the complexity of human communication, particularly in diverse social contexts where individuality and group dynamics shape dialogue. This research fills a gap in the literature by focusing on a contemporary cinematic text that portrays multifaceted characters from varying social strata, thus contributing to studies on communication diversity, minority-majority interactions, and identity expression through language. This study used descriptive qualitative analysis to interpret the data. Following that, the data were analyzed using the Matching technique and the Pragmatic Identity Method to examine the data refers to the context. There were 15 violations of total in the data. It was found, that the results which violates maxim quality with 5 data, 2 data for violations of maxim quantity, 5 data for maxim of manner violations, and violations of maxim relation with 3 data. Both violations of maxim quantity and manner were violated the most in The Batman movie. The results shows that the film’s portrayal of diverse communicative behaviors and enriches our understanding of how pragmatic competence is exercised in complex social interactions. In short, this research underscores the importance of cooperative principles in everyday communication and their strategic manipulation in storytelling to convey nuanced character traits and social tensions.